Modern Cold Spray Materials, Process, and Applications - Villafuerte, Julio (Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the current state of the art of the novel cold spray process.  Cold spray is a solid state metal consolidation process, which allows engineers to tailor surface and shape properties by optimizing process parameters, powder characteristics, and substrate conditions for a wide variety of applications that are difficult or impossible by other techniques.  Readers will benefit from this book's coverage of the commercial evolution of cold spray since the 1980's and will gain a practical understanding of what the technology has to offer.